2007
DOI: 10.1590/s1676-06032007000200028
|View full text |Cite
|
Sign up to set email alerts
|

Chave pictórica para os gêneros de Tabanidae (Insecta: Diptera) do bioma Campos Sulinos, Rio Grande do Sul, Brasil

Abstract: Tabanids were collected and preserved along four years (2002)(2003)(2004)(2005)(2006) in southern Rio Grande do Sul, Brazil. A list of 30 species is presented along with an illustrated key and diagnoses for identification of the 15 genera found in the area. Nine species are registered for the first time in the state of Rio Grande do Sul.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 7 publications
0
8
0
1
Order By: Relevance
“…Species identification was based on Krolow et al The material was deposited in the Entomological Collection'Pe. Jesus Santiago Moure,” Department of Zoology (DZUP), Federal University of Paraná, as well as the Collection of Insects of the Laboratory of Ecology of Parasites and Vectors (COLEPAV), Federal University of Pelotas.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Species identification was based on Krolow et al The material was deposited in the Entomological Collection'Pe. Jesus Santiago Moure,” Department of Zoology (DZUP), Federal University of Paraná, as well as the Collection of Insects of the Laboratory of Ecology of Parasites and Vectors (COLEPAV), Federal University of Pelotas.…”
Section: Methodsmentioning
confidence: 99%
“…In the oriental region of the Pampa biome, 30 species and 15 genera of horse flies were identified (Krolow et al but no conditions were identified that influence population changes over the course of a year. Because of this lack of data, faunistic and ecological studies were initiated to enhance the knowledge of tabanofauna diversity in this part of South America.…”
Section: Introductionmentioning
confidence: 99%
“…They also have biological differences, particularly with respect to the time of appearance and relative abundance. These facts may be linked to the limitations imposed by climate, where altitudes, temperature and humidity can play important roles as balancing factors between different tabanids species populations composing the biocenosis of the different regions as Costa Rica (FaircHild 1961c), Brazilian states of Mato Grosso (Barros et al 2003), Paraná (Bassi et al 2000) and Rio Grande do Sul (KroloW et al 2007). On Ecuador, Diachlorus Osten Sacken, is considered an Andean and sub-Andean genus, with speciation determined by Andes uplift (cárdenas et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Comments: The species occurs in Argentina, Uruguay and Brazil, where it is known from Mato Grosso to Rio Grande do Sul states (KroloW et al 2007;coscarón & PaPavero 2009b) The species feeds on humans, pigs, and horses (Bouvier 1952). This fly lands preferably on horses on the hips, belly, and front legs (Bassi et al 2000), a behavior also observed on Marambaia Island.…”
Section: Tabanus Fuscus Wiedemannmentioning
confidence: 99%
“…The passive capture of tabanids can be obtained on traps such as "canopy" (Schreck et al 1993), "Nzi" (van Hennekeler et al 2008) and "Malaise" (Krolow et al 2007). However, they can be captured actively by manual collection using glass tubes as collectors.…”
mentioning
confidence: 99%